PENDEKATAN KOMUNIKATIF DALAM TES KEMAMPUAN BERBICARA BAHASA ARAB - Eka Dewi Rahmawati (UIN Maulana Malik Ibrahim Malang, 2021)
This study aims to discuss the test of speaking Arabic according to the communicative approach. The type of research used is qualitative research using library research methods or libraries by relying on bibliographic sources in the form of books and scientific journals related to the discussion. Based on the studies that have been done, it is known that the types of language tests in terms of history that appear are discrete, integrative, pragmatic, communicative and authentic tests.There are several forms of tests that use a communicative approach that can be used to measure students' speaking skills, such as the test of telling pictures, be it one picture or series of pictures, telling experiences, interviews, free storytelling and discussion or debate. Student confidence is one of the most important things in running this test. Because with this belief, students will find it easier to speak using Arabic, some students are good at writing but are not good at using it because they do not have self-confidence.